Developing research proposals - Denicolo, Pam; Becker, Lucinda (London : SAGE Publications, Ltd, 2012)
Pam Denicolo and Lucinda Becker recognize the importance of developing an effective research proposal for gaining either a place on a research degree program or funding to support research projects and set out to explore the main factors that that proposal writers need to attend to in developing successful proposals of their own. Developing Research Proposals will help readers to understand the context within which their proposal will be read, what the reviewers are looking for and will be influenced by, while also supporting the development of relevant skills through advice and practical activities. The authors draw together the key elements in the process of preparing and submitting a proposal and concludes with advice on responding to the results, successful or not, and their relevance to future proposals.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Proposal writing in research